Valproic acid alters mitochondrial cholesterol transport in Y1 adrenocortical cells - Brion, L. (2011)
This study demonstrates that VPA increases progesterone production in non-stimulated cells without inducing the levels of Steroidogenic Acute Regulatory (StAR) protein, which facilitates cholesterol transport. This result suggests that VPA increases mitochondrial cholesterol transport through a StAR-independent mechanism and is further supported by the fact that in isolated mitochondria VPA stimulates exogenous cholesterol metabolization to progesterone. VPA also reduces the cAMP-mediated increase of the StAR protein, mRNA levels, promoter activity and progesterone production. In summary, the present data show that VPA can alter steroid production in adrenal cells by a complex mechanism that mainly involves an action on cholesterol access to the inner mitochondrial membrane. The VPA-mediated increase of basal steroidogenesis could be linked to the increase of basal cortisolemia described in patients under VPA treatment.